Compliance improvement in periodontal maintenance - Verônica Franco de Carvalho; Osmar Shizuo Okuda; Carlos Cheque Bernardo; Cláudio Mendes Pannuti; Marco Antonio Paupério Georgetti; Giorgio De Micheli; Francisco Emílio Pustiglioni (University of São Paulo, 2010)
OBJECTIVES: The aim of this study was to assess the infuence of efforts applied to modify the patients' behavior towards periodontal maintenance. MATERIAL AND METHODS: Patients were classifed into three groups: Complete Compliance (participation in all visits), Irregular Compliance (irregular participation, one or more missing appointments), and Noncompliance (abandoned or never returned to the program). Complete compliers received usual procedures of the maintenance visit. The irregular compliers and non-compliers received usual procedures and strategies such as reminding next visit, informing patients on both periodontal disease and importance of maintenance, motivating the patient who showed an improvement in compliance. Thus, 137 patients were observed for 12 months. RESULTS: The degree of compliance has increased signifcantly during this period (p=0.001). No association was detected between age or gender and compliance degree. CONCLUSIONS: The results have shown that the intervention applied had a favorable infuence on the patients' compliance.